The Challenges and Strategies of Social Workers in the Care of the Elderly with Chronic Illness - Tukino (International Journal of Science and Society, 2023)
The objective of the research is to identify, analyse, and understand the challenges faced by social workers in the care of older persons suffering from chronic diseases, as well as to describe and strategies used in addressing them. The research method uses a qualitative approach by conducting in-depth interviews with four social workers who have experience treating elderly people suffering from chronic diseases. The techniques used are interviews and observations, which are then analyzed using content analysis techniques. Research results show that social workers face several significant challenges in the care of older persons with chronic diseases, including the medical complexity of chronic disease, social isolation, mobility constraints, and financial problems. In addition, social workers also face obstacles in coordinating with various health and care services. However, it also developed various effective strategies, such as collaborative approaches with multidisciplinary care teams, intensive emotional support, and providing education to patients and their families. The results of the research can conclude that social workers have an important role to play in addressing the complex challenges in the care of older people with chronic diseases. The strategy applied can help improve the quality of life of patients and support their families in the face of emerging problems.